Consumers’ Satisfaction Toward McDonald’s during Covid-19 Pandemic in Malaysia - Nabilah, Nur Ain; Atiqah, Nur Alyaa; Najwa, Nur Alia; Zulaika, Nur Aliah; Kasih, Julia (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
The purpose of this research was to find out the consumers’ satisfaction towards McDonald’s during the Covid-19 Pandemic in Malaysia based on their service through dine-in, drive-thru, McDonald’s delivery, application, staff, and the food that McDonald’s served to customers. The majority of the information for this study came from the internet. To gain a better knowledge of the study's issue, we looked at a variety of literature reviews, publications, websites, online journals, and paper analyses. As a result, the majority of the customers were satisfied when they dined at McDonald’s because of the environment and the good service from the staff. Most of them are also satisfied using the drive-thru and the delivery that has been provided by McDonald’s because both of them were convenient to use especially during pandemic. Customers are also satisfied using McDonald’s application because there are plenty of offers from McDonald’s for the user. Because of the minority of customers who are dissatisfied with the delivery that have been provided from McDonald’s, the strategy to overcome this problem is to increase the number of delivery points nationwide and make more social media engagement to improve the way how to promote McDonald’s in the future.  Keywords: Convenient, Covid-19, Customers, Environment, Satisfaction,  Social Media.